Factors Influencing Foreign Tourists’ Loyalty in Charter Yachts in Phuket, Thailand - Jonvirat, Ratchukorn; Punyasiri, Sangkae (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2023)
The purpose of this research was to develop and validate the consistency of factors influencing foreign tourists’ loyalty in charter yachts in Phuket, Thailand. The tools used in the research were questionnaires. The sample group consists of 460 foreign tourists with prior experience at one of four marinas: Royal Phuket Marina, Phuket Boat Lagoon, Phuket Yacht Haven Marina, and Ao Po Grand Marina. They also have experience with other charter yachts and have traveled throughout Phuket for at least one night. The statistics used in data analysis were frequency and percentage. The structural equation model is used to investigate causal relationships and determine the path to the causal influence of the four-component variables: 1) perceived marina attributes, 2) tourist perceived value, 3) perceived destination image and 4) perceived tourist satisfaction. The results of the research showed that the causal relationship model was developed in accordance with empirical data. The final predictive coefficient of 35.0 indicates that the variables in the model can explain the variance of the foreign tourists’ loyalty to charter yachts in Phuket, Thailand, by 35 percent. Furthermore, it was found that perceived value had the most influence on international tourists’ loyalty to charter yachts in Phuket.